2021
DOI: 10.1088/1755-1315/910/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Consumers Choice and Preference for Chicken Meat in Sulaymaniyah

Abstract: Chicken meat consumption and demand have significantly increased in the Kurdistan Region of Iraq (KRI) after 2003, which has led to the growth of poultry production and risen import from abroad. Consumer preferences study can be a determinant factor for poultry production development strategies to fill local demand gaps and global market competition. This study aimed to identify the consumer preference of chicken meat regarding the type, size, parts, marketplace, and other vital aspects considered by consumers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The locally produced broiler chicken carcass weights were ranged from 1.58 to 2.57 kg during the last decade (2011 -2020) in Sulaymaniyah governorate. Overall, the average carcass weight was limited to about 2.5 Kg between 2011 to 2018 but then in the last two years, smaller broiler chickens with an average weight of 1.89 kg in 2019 and 1.58 kg in 2020 were produced which may be related to consumer demand and preference as Neima et al, (2021) found that 50% of their respondents had preference for 2-3 Kg weighted whole chicken carcass in Sulaymaniyah.…”
Section: The Trends Of Human Population Growth and Chicken Meat Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…The locally produced broiler chicken carcass weights were ranged from 1.58 to 2.57 kg during the last decade (2011 -2020) in Sulaymaniyah governorate. Overall, the average carcass weight was limited to about 2.5 Kg between 2011 to 2018 but then in the last two years, smaller broiler chickens with an average weight of 1.89 kg in 2019 and 1.58 kg in 2020 were produced which may be related to consumer demand and preference as Neima et al, (2021) found that 50% of their respondents had preference for 2-3 Kg weighted whole chicken carcass in Sulaymaniyah.…”
Section: The Trends Of Human Population Growth and Chicken Meat Supplymentioning
confidence: 99%
“…Regarding previous scientific research studies and reviews on the trends of meat production specifically in the KRI and Sulaymaniyah governorate, only one study has addressed this topic; Neima and Hassan (2020) studied the livestock production tendency in the Sulaymaniyah governorate. Additionally, there are important findings from some other studies regarding consumer choice and preference (Neima, et al, 2021), and the drivers of meat consumption (Abdalla, et al, 2021) in the KRI. Additionally, Dhaghir et al, (2020) showed chicken meat production in their study on the Middle East and North African countries including Iraq.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, it was discovered that Kurdish consumers had a high level of understanding regarding the effects of food on health, which caused the most crucial element in their decision to buy to be the quality of the goods. [11] info@journalofbabylon.com | jub@itnet. Objective: to study the Public awareness toward healthy life: sample from Iraqi community, and study it with some of demographic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Although chicken meat is regularly consumed in the KRI, consumer behaviour towards purchasing and consumption demands have not been considerably quantified yet. Only a few studies have been carried out regarding consumer behaviour and choice for agri-food consumption in the KRI, such as Neima et al (2021), Ali (2021); and Hasan et al (2019). Understanding consumer behaviour assists in formulating food production, price, distribution channels, and sale promotion policies.…”
Section: Introductionmentioning
confidence: 99%